ANALISIS CORAK HISTORIOGRAFI DALAM KARYA SAGIMUN M.D - Hartutik Hartutik (Program Studi Pendidikan Sejarah - Universitas Samudra, 2020)
In the scope of history, of course the term historiography is no stranger to the historical method. One of the historiography products in history is the work of Sagimun Mulus Dumadi (Sagimun MD) with entitled